Scenes and Communities in the City - Klekotko, Marta; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book addresses the problem of creation and reproduction processes of contemporary urban communities, as well as cultural mechanisms and factors of these processes. Rejecting both the environmental determinism, and cultural reductionism of community studies, the book assumes that the postmodern city is a space of diverse urban communities that go far beyond the traditional concept of neighbourhood as well as personal and imagined communities, and thus proposes to comprehend urban community as social practice embedded in urban space. The book applies the Theory of Social Practice and the Theory of Scenes and develops the concept of socio-cultural opportunity structures in order to explain how cultural practices of individuals and symbolic dimensions of territory interact, leading to (re)production of various forms of urban community. It is assumed that culture in general and symbolic meanings of territory in particular, play a crucial role in the process of (re)production of urban communities, that this process takes place in collective cultural consciousness and is mediated by territorially embedded cultural practices of individuals. The book overcomes theoretical gaps in classical community studies and develops a new perspective on urban communal processes based on the analysis of social practices in urban cultural scenes. Marta Klekotko, PhD is sociologist, researcher, university teacher as well as practitioner dedicated to community empowerment and urban development. Her interests cover community studies, urban studies and development studies. She is particularly interested in cultural mechanisms of community empowerment, social cohesion and development - both in theory as well as in practice. In her work, she always takes cultural perspective, fosters theoretical eclectism, and triangulates research methods. She was visiting scholar, among others, at the University of Chicago, State University of New York in Buffalo, and Universityof Barcelona. She is the president of the Research Committee on Community Research (RC03) of the International Sociological Association.
Chapter 1. Introduction -- Chapter 2. Community question: classical debates -- Chapter 3. Urban scenes as community practices -- Chapter 4. Applying urban-scenes-as-community-practices approach: voices from the field -- Chapter 5. Conclusion: scenes approach in community building.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sociology, Urban; Human geography; Urban policy; Urban Sociology; Human Geography; Urban Policy